Low-mold-scale halogen-free flame-retardant polyamide composition and preparation method thereof
By using core-shell structure-modified MCA flame retardant in polyamide materials, the poor flame retardant performance of polyamide materials and mold scale problems in injection molding are solved, and the high performance and low mold scale characteristics of the material are achieved.
Patent Information
- Application Number
- CN202411931816.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-25
AI Technical Summary
Polyamide materials have poor flame retardant properties, which are prone to produce droplets and secondary combustion during combustion, aggravating fire propagation, and at the same time, they are prone to form mold scale during injection molding, affecting production efficiency and cost.
The core-shell structure-modified MCA flame retardant is prepared by hydrogen bond self-assembly and solvent exchange method. Boric acid is introduced to improve the morphology and dispersion of MCA, and the MCA flame retardant is coated with boron-modified phenolic resin to form a core-shell structure, which improves its dispersion and flame retardant properties in polyamide.
It effectively improves the flame retardant properties and mechanical properties of polyamide materials, reduces the formation of mold scale during injection molding, reduces the mold cleaning frequency, and extends the mold usage time.
Smart Images

Figure BDA0005210521990000051 
Figure BDA0005210521990000052
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer material modification, in particular to a low-mold-scale halogen-free flame-retardant polyamide composition and a preparation method thereof. Background Art
[0002] Polyamide materials are widely used in transportation, electrical and electronic, machinery and other industries due to their excellent mechanical properties, solvent resistance, electrical, wear resistance, oil resistance, self-lubrication, corrosion resistance and other excellent properties. At the same time, the flame retardant properties of polyamide materials themselves are poor, and they release a lot of heat when burning, produce molten droplets, cause secondary combustion, and aggravate the spread of fire. In particular, glass fiber reinforced polyamide materials have a "wick" effect due to the glass fiber in the composite material, and the burning speed is fast. At the same time, a large amount of heat is released, which further deteriorates the flame retardant properties. Therefore, it is of great significance to improve the flame retardant properties of polyamide materials while maintaining their excellent comprehensive properties. Melamine cyanurate (MCA) is a nitrogen-based flame retardant that can significantly improve the flame retardant properties of polyamide materials. MCA flame-retardant polyamide materials are widely used in the fields of electrical and electronic and connectors. However, the dispersion performance of MCA in polyamide is not satisfactory, which inevitably further affects the flame retardancy and mechanical properties. In addition, MCA flame-retardant polyamide materials are prone to decompose and precipitate a large number of small molecular substances during injection molding, resulting in mold scale in the mold. During the mass injection molding process of products, production needs to be frequently stopped to clean the mold, which greatly reduces production efficiency and increases production costs.
[0003] Chinese patent CN202210144708.9 adds a specific type of black spot inhibitor and a certain amount of hyperbranched polyester to the MCA flame-retardant polyamide material system, and effectively suppresses the amount of mold fouling generated during the injection molding process of the MCA flame-retardant polyamide material through the synergistic effect of the two, and has high application value in the field of electronic appliances. Chinese patent CN202211598842.2 improves the high-temperature continuous injection molding decomposition problem of nitrogen-based flame-retardant polyamide by screening the particle size distribution of MCA flame retardant ≥ 2 and the water content of MCA flame retardant ≤ 0.2wt%, and improves the injection molding mold fouling performance of the product. Most of the disclosed patents use the conventional method of adding ordinary MCA flame retardants. The poor compatibility of ordinary MCA flame retardants and polyamides leads to poor dispersion performance, which inevitably further affects the flame retardant properties, mechanical properties and serious mold fouling of polyamides, thereby limiting the application scope of polyamide compositions. Summary of the invention
[0004] The present invention aims to provide a low-mold-scale halogen-free flame-retardant polyamide composition and a preparation method thereof.
[0005] The technical solution adopted by the present invention to solve the technical problem is: a low-mold-scale halogen-free flame-retardant polyamide composition and a preparation method thereof, comprising the following components in parts by weight:
[0006] 30-84.8 parts of polyamide resin;
[0007] 5-25 parts of core-shell structure modified MCA flame retardant;
[0008] 10 to 35 parts of filler;
[0009] Compatibilizer 0-5 parts;
[0010] Antioxidant 0.1-1 part;
[0011] Processing aid 0.1-2 parts;
[0012] Masterbatch 0-2 parts.
[0013] In the above polyamide composition,
[0014] The polyamide resin is selected from at least one of PA66, PA56 or PA6.
[0015] The preparation method of the core-shell structure modified MCA flame retardant comprises the following steps:
[0016] (1) Melamine, cyanuric acid, boric acid and deionized water with equal molar mass are prepared into a 25% concentration (mass fraction) solution and placed in a polymerization reactor. The mixture is stirred at a constant temperature of 95° C. for 2 h, and the boric acid-modified MCA is obtained by filtration, drying and grinding.
[0017] (2) The boric acid-modified MCA obtained in step 1 is added to a 5% concentration (mass fraction) solution of a boron-modified phenolic resin and ethanol, and the mixture is stirred for reaction for 2 hours. After adding deionized water of the same volume as the ethanol, the boron-modified phenolic resin is precipitated from the ethanol and coated on the surface of the boric acid-modified MCA obtained in step 1. After filtration, drying and grinding, a core-shell structure modified MCA flame retardant is obtained.
[0018] The water content of the core-shell structure modified MCA flame retardant is ≤0.2wt%, and the phosphorus content is 20-25wt%.
[0019] The filler is a fibrous or non-fibrous filler in terms of form. The fibrous filler is selected from one or more of glass fiber, carbon fiber, basalt fiber, and aramid fiber, and the non-fibrous filler is selected from one or more of whiskers, wollastonite, mica, kaolin, and glass beads.
[0020] The compatibilizer is selected from one or more of SMA resin, SEBS, and EBA-g-MAH.
[0021] The antioxidant is a highly efficient organic copper heat stabilizer that can maintain its original color, is resistant to extraction, does not precipitate, and does not affect CTI.
[0022] The processing aid is selected from one or more of montan wax, polyolefin wax, amide wax, saponified calcium montanate, and saponified sodium montanate.
[0023] The masterbatch is one or more of carbon black, zinc sulfide, iron oxide and aniline black according to the color requirement, the color powder content is 20-99%, and the carrier is PA6 or lubricant.
[0024] The low mold scale halogen-free flame-retardant polyamide composition and the preparation method thereof comprise the following steps:
[0025] (1) weighing a polyamide resin, a core-shell structure modified MCA flame retardant, a compatibilizer, an antioxidant, a processing aid, and a masterbatch according to a ratio and premixing them to obtain a premix;
[0026] (2) adding the premix of step (1) to the main feed port of a twin-screw extruder, adding the filler weighed according to the ratio to the side feed port of the twin-screw extruder, fully plasticizing and mixing at 160-260° C., extruding, cooling and granulating, thereby obtaining the low-molding halogen-free flame-retardant polyamide composition of the present invention.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] The flame-retardant polyamide composition of the present invention is a core-shell structure modified MCA flame retardant prepared by hydrogen bond self-assembly and solvent exchange method. The modified MCA flame retardant introduces boric acid to improve the morphology of MCA and introduces an acid source. On the one hand, boric acid has many hydroxyl groups, which is conducive to participating in the hydrogen bond self-assembly process of MCA, thereby modulating its microstructure. On the other hand, boric acid generated by thermal decomposition of the boric acid modified MCA flame retardant can catalyze the formation of a carbon layer in the matrix. Further, boron-modified phenolic resin is coated on the surface of the boric acid modified MCA flame retardant to form a core-shell structure, which further improves the dispersibility of the flame retardant in polyamide, effectively weakens the interaction between polyamide molecular chains during processing, reduces shear heat, reduces the decomposition of effective components, effectively achieves a balance between uniform dispersion, flame retardancy and mechanical properties, effectively reduces the amount of mold deposit of polyamide materials during injection molding, and is conducive to reducing the frequency of mold cleaning and extending the use time of the mold. DETAILED DESCRIPTION
[0029] The technical solution of the present invention is further illustrated by preferred embodiments below. Without violating the purpose of the present invention, the present invention should not be limited to the contents specifically shown in the following embodiments.
[0030] The examples and comparative examples of the present invention use the following raw materials, but are not limited to the following raw materials:
[0031] Polyamide PA66, trade name EP1106, produced by Huafeng Group Co., Ltd.;
[0032] Polyamide PA56, trade name Ecopent 2260, produced by Shanghai Cathay Biotechnology Co., Ltd.;
[0033] Polyamide PA6, trade name YH800, produced by Yueyang Baling Petrochemical Chemical Fiber Co., Ltd.;
[0034] Melamine, purity ≥99%, commercially available;
[0035] Cyanuric acid, purity ≥99%, commercially available;
[0036] Boric acid, purity ≥99%, commercially available;
[0037] Ethanol, purity ≥99%, commercially available;
[0038] Boron-modified phenolic resin, active ingredient content ≥ 99%, commercially available;
[0039] MCA flame retardant powder, trade name melamine cyanurate (MCA), produced by Shouguang Weidong Chemical Co., Ltd.;
[0040] Glass fiber, trade name ECS301HP-3, produced by Chongqing International Composite Materials Co., Ltd.;
[0041] Processing aid, trade name TP-P1507, produced by Bruggemann;
[0042] Compatibilizer, trade name SMA-800, produced by Jiaxing Huawen Chemical Co., Ltd.;
[0043] Antioxidant, trade name H3377, produced by Bruggemann;
[0044] Antioxidant 1098, hindered phenol antioxidant, commercially available;
[0045] Antioxidant 168, a phosphite antioxidant, commercially available;
[0046] Black masterbatch, trade name PA6-2015, commercially available;
[0047] The preparation methods of the embodiments of the present invention and the comparative examples are as follows:
[0048] The preparation method of the core-shell structure modified MCA flame retardant comprises the following steps:
[0049] (1) Melamine, cyanuric acid, boric acid and deionized water with equal molar mass are prepared into a 25% concentration (mass fraction) solution and placed in a polymerization reactor. The mixture is stirred at a constant temperature of 95° C. for 2 h, and the boric acid-modified MCA is obtained by filtration, drying and grinding.
[0050] (2) The boric acid-modified MCA obtained in step 1 is added to a 5% concentration (mass fraction) solution of a boron-modified phenolic resin and ethanol, and the mixture is stirred for reaction for 2 hours. After adding deionized water of the same volume as the ethanol, the boron-modified phenolic resin is precipitated from the ethanol and coated on the surface of the boric acid-modified MCA obtained in step 1. After filtration, drying and grinding, a core-shell structure modified MCA flame retardant is obtained.
[0051] The water content of the core-shell structure modified MCA flame retardant is ≤0.2wt%, and the phosphorus content is 20-25wt%.
[0052] The preparation method of the low mold scale halogen-free flame retardant polyamide composition comprises the following steps:
[0053] (1) weighing a polyamide resin, a core-shell structure modified MCA flame retardant, a compatibilizer, an antioxidant, a processing aid, and a masterbatch according to a ratio and premixing them to obtain a premix;
[0054] (2) adding the premix of step (1) to the main feed port of a twin-screw extruder, adding the filler weighed according to the ratio to the side feed port of the twin-screw extruder, fully plasticizing and mixing at 160-260° C., extruding, cooling and granulating, thereby obtaining the low-molding halogen-free flame-retardant polyamide composition of the present invention.
[0055] Product performance test method:
[0056] Tensile properties: According to ISO527 method, sample size: 170*10*4mm, test speed 5mm / min;
[0057] Bending performance: According to ISO178 method, sample size: 80*10*4mm, test speed 2mm / min;
[0058] Notched impact performance: according to ISO179 method, sample size: 80*10*4mm;
[0059] Glow Wire Flammability Index (GWFI / 1.0mm): According to the IEC60695-2-12 method, the sample size is 100*100*1.0mm, and the test is carried out according to the method of gradual temperature increase. The starting test temperature is 700℃, and the temperature is gradually increased after the test is passed. The Glow Wire Flammability Index is used to characterize the flame retardant properties of materials.
[0060] Mold deposit: Using an injection molding machine with a mold deposit collector, at an injection molding temperature of 280°C, after 300 consecutive injections, the mold deposit samples in the mold were collected and weighed using an analytical balance to obtain the final mold deposit weight.
[0061] Table 1: Distribution ratios of each group in Examples 1 to 7 (by weight) and related performance test results
[0062]
[0063]
[0064] Table 2: Comparative Example 15 distribution ratio (by weight) and related performance test results
[0065]
[0066] It can be seen from Table 1 and Table 2 that the core-shell structure modified MCA flame retardant polyamide can effectively improve the mechanical properties of the polyamide composition compared with the conventional MCA flame retardant polyamide (Example 1 and Comparative Examples 1-3), improve the risk of the conventional MCA flame retardant system being easily decomposed at high temperature to produce more mold scale (Example 1 and Comparative Examples 2-3), the core-shell structure modified MCA flame retardant has a positive significance for reducing mold scale and improving mechanical properties (Comparative Examples 1-5), the core-shell structure modified MCA flame retardant content is too high will reduce the mechanical properties of the polyamide composition and produce more mold scale (Example 1 and Comparative Example 4), organic copper heat stabilizers produce less mold scale than traditional hindered phenols and phosphite antioxidants (Example 1 and Comparative Example 5). The flame retardant polyamide composition prepared by the present invention has the characteristics of low mold scale and high performance, and can meet the application requirements in the fields of new energy vehicle battery systems, home appliances, and electronic appliances.
Claims
1. A low mold scale halogen-free flame retardant polyamide composition, characterized in that: The composition comprises the following components by weight: 30 to 84.8 parts of polyamide resin, 5 to 25 parts of core-shell structure modified MCA flame retardant, 10 to 35 parts of filler, 0 to 5 parts of compatibilizer, 0.1 to 1 part of antioxidant, 0.1 to 2 parts of processing aid and 0 to 2 parts of masterbatch.
2. The low mold fouling halogen-free flame retardant polyamide composition according to claim 1, characterized in that: The polyamide resin is selected from at least one of PA66, PA56 or PA6.
3. The low mold fouling halogen-free flame retardant polyamide composition according to claim 1, characterized in that: The preparation method of the core-shell structure modified MCA flame retardant comprises the following steps: (1) preparing a 25% concentration (mass fraction) solution of melamine, cyanuric acid, boric acid and deionized water in equal molar mass into a polymerization reactor, stirring and reacting at a constant temperature of 95° C. for 2 h, and obtaining boric acid-modified MCA by filtration, drying and grinding; (2) The boric acid-modified MCA obtained in step 1 is added to a 5% by mass solution of boron-modified phenolic resin and ethanol, and the mixture is stirred for reaction for 2 hours. After adding deionized water having the same volume as that of ethanol, the boron-modified phenolic resin is precipitated from the ethanol and coated on the surface of the boric acid-modified MCA obtained in step 1. After filtration, drying and grinding, a core-shell structure modified MCA flame retardant is obtained.
4. The low mold fouling halogen-free flame retardant polyamide composition according to claim 1, characterized in that: The water content of the core-shell structure modified MCA flame retardant is less than or equal to 0.2 wt %, and the phosphorus content is 20-25 wt %.
5. The low mold fouling halogen-free flame retardant polyamide composition according to claim 1, characterized in that: The filler is a fibrous or non-fibrous filler in terms of form. The fibrous filler is selected from one or more of glass fiber, carbon fiber, basalt fiber, and aramid fiber. The non-fibrous filler is selected from one or more of whisker, wollastonite, mica, kaolin, and glass beads.
6. The low mold fouling halogen-free flame retardant polyamide composition according to claim 1, characterized in that: The compatibilizer is selected from one or more of SMA resin, SEBS and EBA-g-MAH.
7. The low mold fouling halogen-free flame retardant polyamide composition according to claim 1, characterized in that: The antioxidant is a highly efficient organic copper heat stabilizer that can maintain its original color, is resistant to extraction, does not precipitate, and does not affect CTI.
8. The low mold fouling halogen-free flame-retardant polyamide composition according to claim 1, characterized in that: The processing aid is selected from one or more of montan wax, polyolefin wax, amide wax, saponified calcium montanate, and saponified sodium montanate.
9. The low mold fouling halogen-free flame-retardant polyamide composition according to claim 1, characterized in that: The masterbatch is one or more of carbon black, zinc sulfide, iron oxide and aniline black according to the color requirement, the color powder content is 20-99%, and the carrier is PA6 or lubricant.
10. The method for preparing the low mold fouling halogen-free flame-retardant polyamide composition according to claims 1 to 9, characterized in that: The following steps are involved: (1) weighing a polyamide resin, a core-shell structure modified MCA flame retardant, a compatibilizer, an antioxidant, a processing aid, and a masterbatch according to a ratio and premixing them to obtain a premix; (2) adding the premix of step (1) to the main feed port of a twin-screw extruder, adding the filler weighed according to the ratio to the side feed port of the twin-screw extruder, fully plasticizing and mixing at 160-260° C., extruding, cooling and granulating, thereby obtaining the low-molding halogen-free flame-retardant polyamide composition of the present invention.
Citation Information
Patent Citations
MCA flame-retardant polyamide composite material as well as preparation method and application thereof
CN114716812A
A polyamide composite material, its preparation method and application
CN115850964B